2019
DOI: 10.1002/hbm.24719
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of multiple large‐scale brain networks in dementia with Lewy bodies

Abstract: Aberrations of large‐scale brain networks are found in the majority of neurodegenerative disorders. The brain connectivity alterations underlying dementia with Lewy bodies (DLB) remain, however, still elusive, with contrasting results possibly due to the pathological and clinical heterogeneity characterizing this disorder. Here, we provide a molecular assessment of brain network alterations, based on cerebral metabolic measurements as proxies of synaptic activity and density, in a large cohort of DLB patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 102 publications
7
25
0
Order By: Relevance
“…In DLB, metabolic connectivity evidence showed a severe involvement of the posterior cortical, the limbic, and the attention networks, consistently with the pathological and clinical heterogeneity intrinsic to this condition [ 98 ]. DLB connectivity alterations in large-scale resting-state networks are strongly related to the clinical symptoms [ 98 ]. Visual hallucinations (VH) are associated with impaired connectivity in posterior DMN, the attention network, and visual networks [ 66 , 98 ].…”
Section: Molecular and Metabolic Connectivity In Neurodegenerative Conditionsmentioning
confidence: 90%
See 3 more Smart Citations
“…In DLB, metabolic connectivity evidence showed a severe involvement of the posterior cortical, the limbic, and the attention networks, consistently with the pathological and clinical heterogeneity intrinsic to this condition [ 98 ]. DLB connectivity alterations in large-scale resting-state networks are strongly related to the clinical symptoms [ 98 ]. Visual hallucinations (VH) are associated with impaired connectivity in posterior DMN, the attention network, and visual networks [ 66 , 98 ].…”
Section: Molecular and Metabolic Connectivity In Neurodegenerative Conditionsmentioning
confidence: 90%
“…Moreover, isolated rapid eye movement (REM) sleep behavior disorder (iRBD) represents the prodromal stage of full-blown alpha-synucleinopathies [ 94 ]. There are several PET metabolic connectivity studies in PD and DLB [ 66 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], and less evidence in iRBD [ 95 , 102 ] and MSA [ 103 , 104 ].…”
Section: Molecular and Metabolic Connectivity In Neurodegenerative Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A small study (11 patients) from Fujishiro et al showed that hypometabolism in primary visual cortex can predict DLB in non-demented individuals (120). Furthermore, Sala et al showed disruption of posterior cortical networks in DLB patients, especially in the primary visual network (121). Specific disease-related changes in glucose metabolism can be seen in DLB patients even before the development of distinct clinical picture.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%